POLITISASI BIROKRASI PADA PEMILIHAN UMUM KEPALA DAERAH (STUDI MOBILISASI PEGAWAI NEGERI SIPIL DI PEMERINTAH DAERAH KABUPATEN SIAK TAHUN 2011) - Rizki Muharlin Rayadi; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Bureaucratic and political relations in Indonesia has always been volatile. During the New Order, with monoloyality policy, bureaucracy always used as a political machine by the regime power for political mobilization , in order to support the power of the status quo . After the regime fell and was replaced by the era of the Reformation in 1998, there was a fundamental political system , especially the central and local relations . From the pattern of centralized , become more autonomous and decentralized . Likewise, the local elections were originally selected by the DPRD , be elected directly by the people . This change on the one hand gives the positive sense that is to increase the political participation of the people , but on the other hand is causing civil into practical politics. This study seeks to explain why the politicization of the bureaucracy in the elections of regional heads Siak in 2011 and what their impact on government and the bureaucracy . For qualitative research method was chosen by the technique of collecting data through in-depth interviews, which is the key informants in this study is a good class of people who work as civil servants , party officials or politicians , community leaders , entrepreneurs , which have an understanding of the information needed. The results of this study showed that the process of the Election Siak in 2011 , there has been politicization of the bureaucracy in the form of the mobilization of civil servants as a political machine that is used by the regional head candidates who will be contesting the General Election with access to bureaucratic power . Many violations and civil servants involved in practical politics , so the lawsuit and reap Election results do not lead to the creation of bureaucratic neutrality . Bureaucratic politics as a tool or instrument to collect political support for prospective candidates to seize power , It certainly has damaged the spirit of the general election free and fair in the democratic principles contained.Keywords : Politicization, Bureaucracy , civil servants mobilization